2001
DOI: 10.1034/j.1600-0447.2001.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet serotonin transporters and the transporter gene in control subjects, unipolar patients and bipolar patients

Abstract: An association was observed between the polymorphism in intron 2 of the serotonin transporter gene and the number of platelet serotonin transporters. Unipolar patients with a particular genotype had more platelet serotonin transporters than the corresponding controls and bipolar patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
2
24
1
Order By: Relevance
“…However, this finding was not replicated in other Caucasian [139,143,148,149,[169][170][171][172] or an Asian study [157] using independent samples. The rarity of the STin2.9 allele (below 1%) means that the risk attributable to this allele is small.…”
Section: Discussionmentioning
confidence: 81%
“…However, this finding was not replicated in other Caucasian [139,143,148,149,[169][170][171][172] or an Asian study [157] using independent samples. The rarity of the STin2.9 allele (below 1%) means that the risk attributable to this allele is small.…”
Section: Discussionmentioning
confidence: 81%
“…48,59 The 31 papers finally selected reported 43 studies related to the review objective in total since each paper frequently reported several separate studies. In total, 17 population-based studies 9,14,33,34,38,46,50,51,56,60,61,66,[68][69][70] and six family-based studies 12,32,42,53,63,74 were about 5-HTTLPR. A total of 16 population-based studies 27,33,35,38,41,47,[49][50][51]54,56,58,60,61,70,75 and four family-based studies 12,52,57,63 were about the intron 2 VNTR.…”
Section: Resultsmentioning
confidence: 99%
“…46 One did not mention the ethnicity of the study sample. 51 The remaining studies mentioned that the sample was ethnically homogeneous. 9,14,34,35,49,54,58,61,68,70,75 5-HTTLPR meta-analysis In total, 17 population-based studies comprised 1712 cases (ie 3424 alleles) and 2583 controls, whereas six family-based studies comprised 587 trios.…”
Section: Resultsmentioning
confidence: 99%
“…The human gene encompasses 15 exons spanning ϳ31 kb on chromosome 17q11 (Lesch et al, 1994). No differences in amino acid sequence have been found between healthy controls and affective disorder patients, however, associations between two polymorphisms found in noncoding regions of the 5-HTT gene and susceptibility to affective disorder have been reported (Collier et al, 1996;Battersby et al, 1997;Heils et al, 1997;Mellerup et al, 2001;Bellivier et al, 2002). This association, nevertheless, remains controversial because it has not always been reproducible (Hoehe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the different repeat number within the VNTR supports differential expression in vitro (Fiskerstrand et al, 1999;Lovejoy et al, 2003) and both differential and tissuespecific expression in vivo (MacKenzie and Quinn, 1999) in a transgenic model. It has also been demonstrated that the VNTR genotype correlates with the number of platelet 5-HTT transporters in patients with affective disorders (Mellerup et al, 2001). Characterization of the transcription factors that bind to the VNTR and determination of their ability to support differential expression is one approach to identify the signal transduction pathways contributing to neurological disorders in which these 5-HTT intron 2 polymorphisms are implicated.…”
Section: Introductionmentioning
confidence: 99%